2020
DOI: 10.21203/rs.3.rs-96907/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Investigation on the Public's Acceptance of Prevention and Control Measures for COVID-19 in China

Abstract: Background: China has basically succeeded in controlling the COVID-19 epidemic, which is due to the cooperation and acceptance of epidemic prevention measures by the public. However, few studies have examined the measures China has taken to combat COVID-19 in order to reflect on its success in curbing the the spread of epidemic.Methods: In this study, the public acceptance questionnaire was designed based on the epidemic prevention measures adopted in China, to investigate the difference of public acceptance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…[2] As COVID-19 was effectively controlled in China, [1] stricter prevention and control measures were needed to adopt the strategy of "the dynamic COVID-zero" in the phase of normalized prevention and control, so close contacts needed to be interviewed as soon as possible to break the chain of epidemic transmission, creating a great need for personnel to conduct telephone interviews. [5] Some volunteers found it difficult to conduct telephone interviews because of mistrust or unwillingness of the public to cooperate, but they also found that interacting with respondents improved their communication skills. Some volunteers also said that the work was complicated and required good teamwork between departments, because sometimes work procedures changed or work was duplicated between departments, which increased the workload and reduced work efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] As COVID-19 was effectively controlled in China, [1] stricter prevention and control measures were needed to adopt the strategy of "the dynamic COVID-zero" in the phase of normalized prevention and control, so close contacts needed to be interviewed as soon as possible to break the chain of epidemic transmission, creating a great need for personnel to conduct telephone interviews. [5] Some volunteers found it difficult to conduct telephone interviews because of mistrust or unwillingness of the public to cooperate, but they also found that interacting with respondents improved their communication skills. Some volunteers also said that the work was complicated and required good teamwork between departments, because sometimes work procedures changed or work was duplicated between departments, which increased the workload and reduced work efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of the local epidemic had been basically stopped in the normalization stage of the prevention and control of COVID-19, and the aim of the epidemic at that time was to resolutely prevent the continued spread of the epidemic in the communities. [5] In the early period of large-scale transmission and the period of insufficient COVID-19 information, more students felt anxious. [27] We also found that a lack of confidence in their qualifications for voluntary service was the main reason for feeling anxious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation